Marketing research essentials - McDaniel, Carl D. (John Wiley, 2006)
When it comes to putting you on the frontlines of the marketing research industry, McDaniel and Gates stand out from the crowd. These authors deliver the hottest trends, insights, and advances in the field, with a focus on how marketing research is practiced today. Based on their successful Marketing Research, 6th Edition, this paperback text offers the same user-oriented, real-world focus, and cutting-edge content in a more streamlined format. Authors wired to the marketing research industry: Unlike many other marketing research texts, Marketing Research Essentials provides a real-world view of the field from authors who are industry insiders. Together, they bring more than 40 years of marketing research experience to this edition. A strong focus on how to use research: McDaniel and Gates focus on using and analyzing market research results, rather than actually doing the market research....